Predictive value of DNA methylation patterns in AML patients treated with an azacytidine containing induction regimen - Schmutz, Maximilian; Zucknick, Manuela; Schlenk, Richard Friedrich; Mertens, Daniel; Benner, Axel; Weichenhan, Dieter; Mücke, Oliver; Döhner, Konstanze; Plass, Christoph; Bullinger, Lars; Claus, Rainer (Clinical epigenetics, 2023)
Acute myeloid leukemia (AML) is a heterogeneous disease with a poor prognosis. Dysregulation of the epigenetic machinery is a significant contributor to disease development. Some AML patients benefit from treatment with hypomethylating agents (HMAs), but no predictive biomarkers for therapy response exist. Here, we investigated whether unbiased genome-wide assessment of pre-treatment DNA-methylation profiles in AML bone marrow blasts can help to identify patients who will achieve a remission after an azacytidine-containing induction regimen.
Gesehen am 05.03.2024